Pengaruh Pemakaian Alat Ortodontik Cekat Terhadap Keparahan Gingivitis Pada Ibu Hamil di RS PKU Muhammadiyah Surakarta - Sartika, Sherlytania, drg. Edi Karyadi, M.M, drg. S.E. Yuletnawati, M.DSc (2016)
Background: Pregnancy not only effect general health, but also affect oral health specially periodontal tissue. Gingivitis is inflamation gingiva that caused by local and systemic factor. Enhancement estrogen and progesterone hormone concentration during pregnancy caused gingiva more sensitive to plaque. This situation may be aggravated by using fixed orthodontic appliance that acts as a plaque retention factors. Objective: This study aimed was to find out the effect of using fixed orthodontic appliance on the severity of gingivitis on pregnant women in PKU Muhammadiyah Surakarta Hospital. Severity of gingivitis obtained by examination using the Modified Gingival Index (MGI). Methods: This research was an observational analytic used cross sectional method that held on 1st March to 30th April 2016. Sampling using purposive sampling method so it can be obtained 30 pregnant women who ready to be respondent that consist of 15 women who used fixed orthodontic appliance and 15 pregnant women who did not used fixed orthodontic appliance. The results that obtained then tested using SPSS 20.0 for windows with crosstabulation and analyze data using Kolmogorov Smirnov test with confidence interval 95% and the value of p < 0,05 was considered significant. Results: The results of crosstabulation showed that women who did not used fixed orthodontic appliance had mild gingivitis 10 women and moderate gingivitis 5 women, meanwhile that women who used fixed orthodontic appliance had mild gingivitis 2 women, moderate gingivitis 6 women and severe gingivitis 7 women. The results of the test using Kolmogorov-Smirnov test was value of p = 0,028. Conclusion : The conclusion from this research was there were significant effect between severity of gingivitis and using fixed orthodontic appliance in pregnant women in PKU Muhammadiyah Surakarta Hospital.